A Comparative Study of Advanced Oxidation Processes for the Removal of the Antibiotic Sulfadoxine from Water—Transformation Products and Toxicity - Panagiotis A. Bizirtsakis; Kyriaki Anagnostopoulou; Vasilis C. Sarasidis; Panagiota Petsi; Alexandra Moschona; Konstantinos V. Plakas; Dimitra A. Lambropoulou (Applied Sciences)
Sulfonamides, including sulfadoxine (SDX), are widely used antibiotics, particularly for malaria treatment. However, their extensive use has led to environmental pollution, microbial resistance, and public health risks. Advanced Oxidation Processes (AOPs) offer promising methods to degrade such pollutants in water, though they may generate more toxic by-products. This study evaluates three AOPs with different hydroxyl radical generation principles: the Fenton reagent (H2O2/Fe2+), hydrogen peroxide photolysis (UV-C/H2O2), and heterogeneous photocatalysis (UV-A/TiO2). Heterogeneous photocatalysis showed superior performance, achieving 100% degradation and 77% mineralization under optimized conditions. Further analysis explored the effects of UV dose, catalyst concentration, and pH on process efficiency. The influence of water matrices, including Ultrapure Water (UW), Tap Water (TW), and Surface Water (SW) from the Aliakmonas River, was also examined. High-Resolution Mass Spectrometry identified 11 SDX transformation products formed during photocatalysis, with their formation mechanisms reported for the first time. An ecotoxicity assessment using ECOSAR software revealed insights into the potential environmental impact of these by-products.